Eine Geschichte zweier Nationalismen: Die Bedeutung gesellschaftlicher Strukturen für Irans Grüne Bewegung - Harris, Kevan; McHardy, Julien (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
In contrast to simplified stories in Western media, the conflict between the Iranian government and the oppositional „green” movement is analyzed as a conflict between two „new” (i.e. post-revolutionary) classes. Both classes rely heavily on different kinds of nationalism.